Teaching Reading Skills in Applying EUQP Method and Dealing with The Problem in SMP Plus Putra Indonesia - Zahra, Nurul Fatimah (English Journal Antartika, 2023)
The research investigates the effectiveness and identifies the impact of utilizing the explanation, understanding, questions, and pronunciation (EUQP) strategy in teaching reading comprehension in descriptive and narrative texts. The research was conducted at SMP Plus Putra Indonesia for two months, using a descriptive and qualitative research design. Data collection involved interviews, analysis, and perception, while data analysis was conducted through topic examination and alignment with the research questions. The findings revealed that the utilization of the EUQP method led to an improvement in students' reading comprehension in both descriptive and narrative texts. The study highlighted the significance of teaching reading skills and the positive impact of the EUQP method on students' reading comprehension. This research contributes to the existing literature on strategies for enhancing students' reading comprehension, particularly in descriptive and narrative texts for different grade levels. The combination of explanation, understanding, questions, and pronunciation methods proved to be effective in improving students' reading skills.